Alcohol and Aldehyde Dehydrogenases Contribute to Sex-Related Differences in Clearance of Zolpidem in Rats - Peer, Cody J.; Strope, Jonathan D.; Beedie, Shaunna; Ley, Ariel M.; Holly, Alesia; Calis, Karim; Farkas, Ronald; Parepally, Jagan; Men, Angela; Fadiran, Emmanuel O.; Scott, Pamela; Jenkins, Marjorie; et al. (Frontiers in Pharmacology, 2016)
Objectives:  The recommended zolpidem starting dose was lowered in females (5mg vs 10mg) since side effects were more frequent and severe than those of males; the mechanism underlying sex differences in pharmacokinetics (PK) is unknown.  We hypothesized that such differences were caused by known sex-related variability in alcohol dehydrogenase (ADH) expression. Methods:  Male, female, and castrated male rats were administered 2.6 mg/kg zolpidem, +/- disulfiram (ADH/ALDH pathway inhibitor) to compare PK changes induced by sex and gonadal hormones.  PK analyses were conducted in rat plasma and rat brain. Key findings:  Sex differences in PK were evident: females had a higher CMAX (112.4 vs 68.1 ug/L) and AUC (537.8 vs 231.8 hr*ug/L) than uncastrated males.  Castration induced an earlier TMAX (0.25 vs 1 hr), greater CMAX (109.1 vs 68.1 ug/L), and a corresponding AUC increase (339.7 vs 231.8 hr*ug/L).  Administration of disulfiram caused more drastic CMAX and TMAX changes in male vs female rats that mirrored the effects of castration on first-pass metabolism, suggesting that the observed PK differences may be caused by ADH/ALDH expression. Brain concentrations paralleled plasma concentrations. Conclusions:  These findings indicate that sex differences in zolpidem PK are influenced by variation in the expression of ADH/ALDH due to gonadal androgens.